Social Actions of Juvenile Delinquency in the Illegal Racing Phenomenon - Muhammad Triesnabayu; Siti Khumayah; Aghnia Dian Lestari (CV. Media Digital Publikasi Indonesia, 2026)
The spread of juvenile street illegal car races among teenagers has raised the attention and then delinquency aspects as well, which stems from weak social reinforcement (control) factors, interpersonal communication defect in the family and missing fields for good interests. This research seeks to examine the kinds of social interaction among illegal street racers, investigate their motivations for involvement and uncover the symbolism underlying the interactions of the community of outlaw street racers. The research method is descriptive qualitative approach with phenomenology pattern and using Max Weber's Social Action theory as an analysis model. Data were collected from direct observation, in-depth interviews, documentation of the participants and their families and surroundings as well as garage owners’ sources. The study’s findings suggest that illegal street racing is not only deviant behaviour, but it also serves as a symbolic means of communication where teenagers establish and present their identity, voice membership in society, group loyalty. This is adolescents’ “deprivation of social existence” and VIP room of self-realization. Thus, moves to combating this must be through mutually sympathetic and educational communication and for it ever to work: long enough sticks and comfortably placed legal outlets for these interests of automotive controversy.